Zambia: A quiet crisis in African research and development - Elliott, Howard; Perrault, Paul T. (International Food Policy Research Institute, 2006)
The evolution of agricultural research and development policy in Zambia is emblematic of the quiet crisis in African agricultural research. Zambia, a medium-sized country that has avoided internal conflict, has, until recently, been spared from natural disasters. It has also enjoyed periods of relative economic well-being and institutional growth based on its copper industry. Zambia has a number of distinct agricultural regions that generally have good (but not always effective) access to water resources and promising agricultural potential. This potential has not been realized because of post-independence national policies that involved a suite of state interventions, which became unsustainable with falling copper revenues. In the past decade, Zambia has largely adhered to structural adjustment measures; however, as a consequence, its agricultural R&D institutions have lost significant key resources and subsequently credibility, when the research agenda failed to evolve quickly enough to respond to, much less lead, the changes in the economy.